Short-Term Heat Shock Affects Host–Virus Interaction in Mice Infected with Highly Pathogenic Avian Influenza Virus H5N1 - Xue, Jia; Fan, Xiaoxu; Yu, Jing; Zhang, Shouping; Xiao, Jin; Hu, Yanxin; Wang, Ming (Frontiers in Microbiology, 2016)
Highly pathogenic avian influenza virus (HPAIV) H5N1 is a highly contagious virus that can cause acute respiratory infections and high human fatality ratio due to excessive inflammatory response. Short-term heat shock, as a stressful condition, could induce the expression of heat shock proteins that function as molecular chaperones to protect cells against multiple stresses. However, the protective effect of short-term heat shock in influenza infection is far from being understood. In this study, mice were treated at 39°C for 4 h before being infected with HPAIV H5N1. Interestingly, short-term heat shock significantly increased the levels of HSP70 and pro-inflammatory cytokines IL-6, TNF-α, IFN-β and IFN-γ in the lung tissues of mice. Following the HPAIV H5N1 infection, short-term heat shock alleviated immunopathology and viral replication in lung tissue and repressed the weight loss and increased the survival rate of H5N1-infected mice. Our data reported that short-term heat shock presented beneficial anti-HPAIV H5N1 properties in mice model, which offers an alternative strategy for non-drug prevention for influenza infection.